Ancient Egyptian technology and innovation : transformations in pharaonic material culture - Shaw, Ian, 1961- (BCP Egyptology., 2012)
This book examines the fundamental evidence for many different aspects of change and evolution in ancient Egyptian technology. It includes discussion of the wider cognitive and social contexts, such as the Egyptian propensity for mental creativity and innovation, and the pace of change in Egypt in comparison with other African, Mediterranean and Near Eastern states. This book draws not only on traditional archaeological and textual sources but also on the results of scientific analyses of ancient materials and on experimental and ethno-archaeological information. Case-studies analyse those.